Persepsi Santriwati Dalam Pembelian Kosmetik Berlabel Halal - Agus Alimuddin; Lisda Aisyah; Risa Alvia (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2022)
Halal products have bruised the world of marketing with many products labeled halal. Among them are halal cosmetics, but it is very unfortunate that there are halal products but not labeled halal. One of them is a medical product that has a business license, registered with BPOM, not even harmful by its users but does not hold a halal label permit. The method used is qualitative, using a sociological approach to economics whose purpose is to find out that a product labeled halal or halal cosmetics can not only be seen from the label but certain few that can be used as a benchmark of a halal product. The results of this study show that halal labels in cosmetics on the market provide a choice of buying interest so that with the attitude that there are several roles that occur in halal certification including the role of religious identity, attitudes, subjective norms or perceived behaviour control that can produce a positive or negative role in the interest in buying products.